Hubungan gaya hidup dengan Fungsi kognitif pada lansia - Agustia, Shafrina -; Sabrian, Febriana -; Woferst, Rismadefis - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to identify the correlation of lifestyle and cognitive function in the elderly in Kelurahan Tuah Karya Kecamatan Tampan Pekanbaru. The design was descriptive correlational research with cross sectional approach. The sampling technique was cluster sampling, stratified random sampling and convenience sampling with 97 elderly which was selected based on inclusion criteria. This research used questionnaire for lifestyle variable and Mini Mental State Examination (MMSE) that was developed by Folstein MF (1975) in Brunner and Suddarth (2002) for cognitive function variabel. The univariate analysis was done by looking at the distributions of frequencies and bivariate analysis was done by using chi-square test. The result showed that from 51 respondents with healthy lifestyle, that were 47 respondents (92,2%) with normal cognitive function,Â  4 respondents (7,8%) with probable cognitive impairment, and no one with definitive cognitive impairment (0%). Respondents who had unhealthy lifestyle were 46, and from that number 26 respondents (56,6%) had a normal cognitive function,Â  20 respondents (43,5%) had probable cognitive impairment, and no one had definitive cognitive impairment (0%). The statistic showed p value (0,000) < alpha (0,05). It means that there is a correlation between lifestyle and cognitive function of elderly in Kelurahan Tuah Karya Kecamatan Tampan Pekanbaru. Keywords: cognitive function, elderly, lifestyle, MMSE